Factors Associated with Management of Workplace Violence Competence Among Chinese Nursing Interns - Meng L; He L; Ouyang L; Fu M; Li P; He Y (Risk Management and Healthcare Policy)
Lingyao Meng,1,2 Lifang He,1 Lu Ouyang,3 Mengxue Fu,2 Pan Li,1,* Yongmei He1,* 1School of Nursing, Xiangnan University, Chenzhou, 423000, People’s Republic of China; 2College of Nursing and Allied Health Sciences, St. Paul University Manila, Manila, Philippines; 3Bidding Center, Xiangya Hospital, Central South University, Changsha, 410008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pan Li, School of Nursing, Xiangnan University, Chenzhou, 423000, People’s Republic of China, Tel +86 17773560292, Email lipan1020@xnu.edu.cn Yongmei He, School of Nursing, Xiangnan University, Chenzhou, 423000, People’s Republic of China, Tel +86 13873566000, Email hlxyhym@163.comPurpose: The cases of workplace violence (WPV) experienced by nurses and nursing students in recent years has become alarming high. However, managing and developing WPV competence among nursing students remain underreported. Therefore, this study investigated the current status of management of workplace violence competence (MWVC) and identify associated factors affecting their MWVC among nursing interns.Participants and Methods: A total of 817 nursing interns from six tertiary hospitals in Hunan Province, China, participated in this study in July 2023. Data were collected via online survey questionnaires using the Management of Workplace Violence Competence Scale (MWVCS), the Patient Risk Identification Ability Assessment Questionnaire, and the Professional Identity Questionnaire for Nursing Students (PIQNS).Results: Among participants, 91.1% were female (n=744), 68.1% (n=556) were between 21 to 23 years old, and 54.1% (n=442) obtained a bachelor’s degree. The score of management of workplace violence competence was 123.25 (SD=11.06). The multiple linear regression analysis showed that the diploma degree (B=3.152, p< 0.001, 95% CI: 2.087– 4.217), witnessed a workplace violence incident in a hospital (B=4.274, p< 0.001, 95% CI: 3.164– 5.384), trained in WPV prevention skills (B=7.196, p< 0.001, 95% CI: 6.007– 8.386), patient risk identification ability (B=1.006, p< 0.001, 95% CI: 1.163– 0.893), and professional identity (B=0.693, p< 0.001, 95% CI: 0.571– 0.815) were the associated factors of MWVC among nursing interns.Conclusion: The MWVC among nursing interns was at an intermediate level. To enhance MWVC, it is recommended to strengthen WPV prevention and management training, particularly for interns with diploma degrees, no experience witnessing WPV incidents, no prior training in WPV prevention skill, and lower levels of patient risk identification ability and professional identity. Our findings may guide the establishment of focused training programs and support measures to improve interns’ capacity to manage WPV, increasing their professional growth and mental health while giving significant insights and intervention techniques for nursing educators and managers.Keywords: nursing interns, management workplace violence competence, patient risk identification ability, professional identity, associated factors